(untitled) (Iris Journal of Scholarship, 2019)
A school-based enterprise (SBE) is an entrepreneurial operation managed and operated by students in a school setting. School-based enterprises reinforce classroom instruction through practice-based learning and can enhance creativity, innovation, problem-solving, critical thinking, and other skills. In addition to creating a more engaging, enriching learning environment, SBE bridges the gap between classroom instruction and the world of work and can benefit students, schools, and communities. This paper utilized the systems view of school climate framework to assess differences in perceptions of school climate between students participating in SBE and students not participating in SBE at a high school in the Mississippi River Delta Region. The qualitative analysis of five focus groups with 36 students examined differences in relationships, values, and beliefs and findings indicated that SBE can produce more meaningful, enriching learning experiences than students not participating in SBE. This research adds to the sparse empirical analyses of SBE and suggests directions for future inquiry.